Inferior mesenteric artery aneurysm in the setting of celiac and superior mesenteric artery occlusion - Tan, Corinne (J Vasc Surg Cases Innov Tech, 2019)
Inferior mesenteric artery (IMA) aneurysm is a rare type of visceral aneurysm. We present the case of a 77-year-old woman with an IMA aneurysm in the setting of chronic complete occlusion of the origins of her celiac artery and superior mesenteric artery. The patient was managed successfully with surgical excision of the IMA aneurysm with an end-to-side anastomosis of the IMA to the left common iliac artery. The case report is followed by a discussion based on a literature review of the few previously reported occurrences of IMA aneurysm.